2023
DOI: 10.3390/ijerph20156513
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Long COVID: A Comparative Study of Exercise Rehabilitation Benefits in Patients with Long COVID, Coronary Artery Disease and Fibromyalgia

Claire Colas,
Yann Le Berre,
Marie Fanget
et al.

Abstract: Exercise in long COVID is poorly studied. Nevertheless, exerciserehabilitation could improve cardiorespiratory, muscular and autonomic functions. We aimed to investigate improvement in physical and autonomic performances of long COVID patients (n = 38) after a 4-week exercise rehabilitation program (3 sessions/week) compared to two control groups composed of coronary artery disease (n = 38) and fibromyalgia patients (n = 38), two populations for whom exercise benefits are well known. Efficacy of exercise train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Although different methodologies were used, both concluded that long COVID influences the quality of life of those with the disease hindering same. It is important to note that, although they are distinct entities, long COVID shares some similarities in terms of symptoms and challenges in diagnosis and treatment with other conditions, such as fibromyalgia ( 15 , 38 , 39 ). Furthermore, studies have also shown that long COVID, fibromyalgia and chronic fatigue syndrome are more prevalent among females ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although different methodologies were used, both concluded that long COVID influences the quality of life of those with the disease hindering same. It is important to note that, although they are distinct entities, long COVID shares some similarities in terms of symptoms and challenges in diagnosis and treatment with other conditions, such as fibromyalgia ( 15 , 38 , 39 ). Furthermore, studies have also shown that long COVID, fibromyalgia and chronic fatigue syndrome are more prevalent among females ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on developing the most appropriate exercise protocol for patients with PCC, ranging from strength and endurance exercises to combined aerobic and resistance training [22,50,51], which can be varied in intensity and duration, and all show improvements in functional capacity [17,52].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that patients with prolonged COVID symptoms are more likely to have obesity and any obesity degree (BMI ≥ 30 kg/m 2 ) was associated with a worse PCC prognosis [16]. Thus, an intensive multidisciplinary, tailored rehabilitation approach is required to maximize the patient's functional recovery and facilitate the returning to premorbid life, especially when PCC symptoms appear to persist or even worsen in susceptible individuals [17].…”
Section: Introductionmentioning
confidence: 99%